On the Development of Focused Ultrasound Liquid Atomizers - Jumaily, Ahmed M. Al; Meshkinzar, Ata (Advances in Acoustics and Vibration, 2017)
This paper reviews the evolution of focused ultrasonic transducers of various kinds for fluid atomization and vaporization. Ultrasonic transducers used for atomization purposes in biomedical, pharmaceutical, or industrial applications, such as surface acoustic wave (SAW) transducers, array of micromachined nozzles, and Fourier horn micromachined nozzles with or without a central channel, are all presented and compared. For simplicity of manufacturing and low cost, we focus on plates and curved and corrugated structures for biomedical humidification.